Maksimalisasi Anggaran Sebagai Tolak Ukur Kepuasan Konsumi Dalam Pandangan Ekonomi Islam - Aswin, Aswin; Nurdin, Muhammad (Universitas Islam Negeri Sumatera Utara, 2024)
This study defines consumption as using products and services, but it also emphasizes how crucial it is to addressing personal needs. The purpose of this study is to examine how budget maximization is viewed as a gauge of consumer happiness in Islamic economics. This research methodology combines a review of the literature with a qualitative approach. The study's findings demonstrate how, in the Islamic economic perspective, consuming is seen as a way to satisfy people's basic requirements. Religion is a major factor in influencing people's consumption decisions. Strong religious convictions will influence consumption in a significant way, affecting both this world and the afterlife.